High performance quantum key distribution prototype system using a commercial off-the-shelf solution: experimental and emulation demonstrations - López-Leyva, Josué Aarón; Ruiz Higuera, Jesús; Arvizu Mondragón, Arturo; Santos Aguilar, Joel; Ramos García, Raúl; Ponce Camacho, Miguel Ángel (My University, 2017)
A continuous variable-quantum key distribution system prototype that uses weak coherent states with a diffused phase, commercial off-the-shelf devices, complete free space 90-degrees hybrid and simplified quantum protocol is proposed in this paper. In general, the quantum transmitter-re- ceiver shows an experimental average quantum bit error rate of 30% using auto-homodyne detec- tion with 0.25 photons per pulse in locking phase mode. The emulated final secret key rate measurements were 20 and 40 Kbps for minimum (30 Mbps) and maximum (90 Mbps) throughput, respectively, in a real traffic network using databases for the quantum keys generated by two true random number generators.
Optica Applicata Journal
Keywords: Quantum cryptography; Final secret key rate (FSecKR); Coherent states